Du règlement échelonné - Bolduc, Jacques (Assurances, 1982)
Structured settlements represent a new way to settle accident claims and offer considerable advantages bath for the claimant and the Insurer. Such settlements guarantee the victim or his or her dependants a series of periodic payments issued for the purpose of satisfying specific needs in the years to come. These payments maybe fixed or variable and may be paid out over an extended period of time. Since the beneficiary benefits from a special income tax arrangement, he or she may enjoy a more generous settlement and the Insured, by paying out indemnities in structured settlements, may at the same time substantially reduce costs.